Cobalt-Doped Silica Organic-Inorganic Materials by Sol-Gel Method: Preparation and Thermal Stability Calcined under N2 Atmosphere. Issue 1 (2nd September 2021) - Yang, Jing; Ai, Yuzhi; Fan, Wangqing; Mu, Ruihua; Chen, Xi; Hou, Haiyun
Abstract: Cobalt-doped silica organic-inorganic (Co/SiO2 ) materials were prepared by sol-gel technique using tetraethylorthosilicate (TEOS) and methyltriethoxysilane (MTES) as silicon precursors and Co(NO3 )2 ·6H2 O as cobalt source. The influence of calcination temperature on the microstructure of Co/SiO2 material under N2 atmosphere was discussed by X-ray Diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), energy dispersive spectrum (EDS) and thermogravimetric-differential thermogravimetric (TG-DTG) measurements. The results showed that, when calcined at N2 atmosphere, the Co element in the Co/SiO2 material exists not only as the Si-O-Co bond, but also the crystals containing the cobalt element. In the calcing process of 25 ∼ 800 °C, the crystals containing the cobalt element have successively undergone four phase transitions from Co(NO3 )2 ·6H2 O to Co3 O4, CoO and elemental Co 0 . The Si-O-Co bonds were formed in the calcined Co/SiO2 materials. The water contact angle on the Co/SiO2 film surface achieved the maximum value of 95.6° when the calcination temperature is at 400 °C. In order to keep the hydrophobicity of Co/SiO2 membrane materials for gas separation, the optimal calcination temperature should be 350 ∼ 400 °C. The Co/SiO2 membrane material calcined at 400 °C has a larger specific surface area, pore volume and mean pore diameter than the SiO2 sample.